Художній образ як центральний компонент структури літературного твору - Удяк, Галина; Udiak, Halyna (Східноєвропейський національний університет ім. Лесі Українки, 2014)
Статтю присвячено проблемі однієї із центральних категорій поетики – художнього образу у європейській культурно-літературній традиції. Автор підкреслює, що кожен літературний твір – це система художніх образів, а саме у художніх образах втілений найважливіший ідейно-естетичний сенс художньої цілісності твору. Великого значення для розуміння та осмислення суті художнього образу автор надає дослідженням візантійських мислителів, О. Потебні, І. Фізера, Г. Шпета, М. Бахтіна, В. Беньяміна, Р. Барта. The article is devoted to the problem of one of the central categories of poetics – the artistic image in the European cultural and literary tradition. A great importance for the understanding and comprehension of the essence of the artistic image is attached to the researches of Byzantine thinkers who used the term “beautiful” close to the notion “image” like a materialized reflection of the transcendent idea. In the Ukrainian study of literature the author first of all has mentioned Oleksandr Potebnya’s fundamental doctrine about a verbal artistic image. In the article the reception of Oleksandr Potebnya’s ideas in the American (Ivan Fizer) and West-European (Renate Lachmann) study of literature is investi¬gated. Among Russian literary critics, who in many respects in a new way interpreted the problem of the artistic image and summarized a great experience of Western study of literature, the name of Mikhail Bakhtin is mentioned. A special attention is paid to the problem of the notion of the image, which takes the place between an allegory and a symbol, by Walter Benjamin. Rolan Bart’s notion of the image is analyzed by the example of an advertisement.
The Artistic Image as a Central Component of the Structure of a Literary Work
Keywords: художній образ; слово; літературний твір; літературознавство; проблема; artistic image; word; literary work; study of literature; problem